Asthma exacerbation prevalence during the COVID-19 lockdown in a moderate-severe asthma cohort - de Boer, Geertje (BMJ Open Respir Res, 2021)
INTRODUCTION: Following the recent COVID-19 lockdown, a reduction in emergency healthcare visits was reported. Infectious diseases were less often diagnosed, while it was not clear if this was due to a decrease in prevalence or a decrease in emergency healthcare visits due to fear of COVID-19. METHODS: This study comprises a follow-up from a recently finished randomised controlled trial, to gain insight into the prevalence of asthma exacerbation and fear of COVID-19 in patients with moderate-severe asthma and controls in the Netherlands. Participants, patients with asthma and controls, were invited to fill out a short survey by email or post. Exacerbation frequencies until 1 July 2020 were verified with the hospitals’ and general practitioners’ medical records, pharmacies and patient interviews. RESULTS: In quarter 2 of 2020, mean exacerbation frequency per patient was significantly lower (χ(2)(3)=9.91, p=0.019) compared with quarter 2 in previous years. Patients with asthma were more likely to avoid (38.8%; controls, 0.0%, p<0.01) or delay (24.5%; controls, 0.0%, p=0.02) essential medical visits due to fear of SARS-CoV-2 infection at medical facilities. CONCLUSION: In conclusion, we found a significantly reduced asthma exacerbation frequency during COVID-19 social distancing measures compared with previous years. Patients with asthma also showed more anxiety towards (acquiring) COVID-19 infection. TRIAL REGISTRATION NUMBER: NL8576.